Environmental aspects of the safety of civil aviation of Ukraine - Боярська, З. І. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article examines state regulation of environmental safety of civil aviation in Ukraine.